Free Verses in Balochi Literature: An Experience in Form - Ullah, Saeed; Gul, Nasreen (sourcecoder, 2024)
The beginning and development of modern Balochi poetry took place in the early 1950s. During this period, along with other poetic genres, free verse was also introduced in Balochi poetry. Modern Balochi poetry has seen some of the best thematic and poetic experiences in free verse. Poets such as Azad Jamaldini, Malik Toqi, Ata shad, Akbar Barakzai, Siddiq Azath, Ashraf Sarbazi and some other poets have played a significant role in the promotion of free verse. The most prominent poet who took Baloch free verse in high stages was Atta Shad. Before Atta Shad, Balochi free verse traditionally was limited with a few political and progressive thoughts of subject materials. Atta Shad did not expend it in matter of objectivity but also promoted it in regards with art and aesthetics. This research paper thoroughly examines the history and tradition of free verse in Balochi poetry, as well as the various experiences within this form from the very inception till up to date.